2014
DOI: 10.1088/0951-7715/27/2/227
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal spectrum of self-similar measures with overlap

Abstract: It is well known that the multifractal spectrum of a self-similar measure satisfying the open set condition is a closed interval. Recently, there has been interest in the overlapping case and it is known that in this case there can be isolated points. We prove that for an interesting class of self-similar measures with overlap the spectrum consists of a closed interval union together with at most two isolated points. In the case of convolutions of uniform Cantor measures we determine the end points of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 13 publications
0
47
0
Order By: Relevance
“…This completes the proof. We remark that ( √ m 2 + 4−m)/2 < 1/m, so this improves upon the fact that the local dimension of the m-fold convolution of the uniform Cantor measure on the Cantor set with ratio 1/m has an isolated point at 0, as shown in [2,20]. Note that when ̺ = 1/(m + 1), the IFS satisfies the open set condition and hence there is no isolated point.…”
Section: Isolated Points In the Set Of Local Dimensionsmentioning
confidence: 67%
“…This completes the proof. We remark that ( √ m 2 + 4−m)/2 < 1/m, so this improves upon the fact that the local dimension of the m-fold convolution of the uniform Cantor measure on the Cantor set with ratio 1/m has an isolated point at 0, as shown in [2,20]. Note that when ̺ = 1/(m + 1), the IFS satisfies the open set condition and hence there is no isolated point.…”
Section: Isolated Points In the Set Of Local Dimensionsmentioning
confidence: 67%
“…Indeed, in [12], Hu and Lau discovered that when µ is the three-fold convolution of the classic middle-third Cantor measure on R, then there is an isolated point in the set of local dimensions, namely at x = 0, 3. This fact was later established for other 'overlapping' Cantor-like measures in [1,6,7,15].…”
Section: Introductionmentioning
confidence: 65%
“…In [1], it was shown that the sets of local dimensions for quotients of k-fold convolutions of Cantor measures with contraction factor 1/d are intervals whenever k ≥ d. Although these quotient measures do not have an essential class of positive type, we are able to modify our general approach to give a new proof of this fact. Moreover, we extend this result to what we call complete quotient Cantor-like measures and also prove that the set of local dimensions is the closure of the set of local dimensions of periodic points.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We call these self-similar Cantor-like measures, (m, d)-measures, and refer to them as uniform if all p i are equal. The dimensional properties of these measures are also of much interest; see, for example, [5,13,17,20]. We use combinatorial techniques to find an (explicit) analytic function T with the property that the Garsia entropy of the uniform (m, d)-measure is given by T (1)/ log 2 d when 2 ≤ d < m ≤ 2d − 1.…”
Section: Introductionmentioning
confidence: 99%